ANALISIS TRANSPARANSI DAN AKUNTABILITAS OTONOMI DESA DALAM PENGELOLAAN DAN PERTANGGUNGJAWABAN ALOKASI DANA DESA DI DESA KAUNERAN SATU KECAMATAN SONDER KABUPATEN MINAHASA - Tambuwun, Fernando Victory; Sabijono, Harijanto; Alexander, Stanly W. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The allocation of village funds is funds allocated by the district/municipality governments for villages sourced from the state budget and revenues or central and regional fiscal balances funds, used to finance the implementation of governance, development implementation, community development and community empowerment. The grant of village funds is done in several stages budgeting, allocation, distribution, use, reporting, and monitoring or evaluation of village funds. The objectives of this research is to find out the mechanism of channeling the allocation of village funds in the kauneran village of one of the subdistricts of sonder of minahasa district and to know the constraints faced in the tranparency and accountibility of the management of the village fund allocation in th kauneran village of one district of minahasa regency. The results of this study indicate that transparency and accountibility of gradual allocation of village funds from budgeting, allocation, use, reporting, and monitoring or evaluation work well.Keywords : Allocation of village funds, Transparency, Accountibility